Does impedance matter when recording spikes with polytrodes? - Neto, Joana P. (2019)
This work was supported by funding from the European Union's Seventh Framework Programme (FP7/2007-2013) Grant Agreement 600925, the Bial Foundation Grant 190/12 and the FCT-MCTES Doctoral Grant SFRH/BD/76004/2011 (to JN).